Lower bound on the electroweak wall velocity from hydrodynamic instability - Megevand, Ariel Hugo (2015)
The subsonic expansion of bubbles in a strongly first-order electroweak phase transition is a convenient scenario for electroweak baryogenesis. For most extensions of the Standard Model, stationary subsonic solutions (i.e., deflagrations) exist for the propagation of phase transition fronts. However, deflagrations are known to be hydrodynamically unstable for wall velocities below a certain critical value. We calculate this critical velocity for several extensions of the Standard Model and compare with an estimation of the wall velocity. In general, we find a region in parameter space which gives stable deflagrations as well as favorable conditions for electroweak baryogenesis.